Comparison of Tumor Cell Responses to Different Radiotherapy Techniques: Three-Dimensional Conformal Radiotherapy (3D-CRT), Volumetric Modulated Arc Therapy (VMAT), and Helical Tomotherapy (HT) - Phanwadee Kasetthamrongrat; Rinwarat Phumsankhot; Aphidet Duangya; Anirut Watcharawipha; Wannapha Nobnop; Narongchai Autsavapromporn (Biology)
Currently, advanced RT techniques such as VMAT and HT are being developed to optimize tumor coverage while minimizing radiation exposure to the surrounding organs that are at risk. Despite their growing clinical use, comparative studies evaluating the dosimetric and radiobiological effects of these modalities remain limited. In this study, A549, HeLa, and HepG2 cells were exposed to a single 2 Gy dose, using three RT techniques (3D-CRT, dual arc VMAT, and HT). Treatment plans were generated using a water phantom to ensure consistent target coverage and comparable dosimetric parameters across the techniques. Multiple radiobiological endpoints were assessed to evaluate the cellular responses. Although all three techniques yielded similar dosimetric parameters without statistically significant differences, the biological responses varied among the cell lines. Notably, VMAT and HT demonstrated superior tumor cell suppression compared to 3D-CRT. This was likely due to their enhanced dose conformity and modulation precision, which potentially led to improved tumor cell killing. These findings highlight the importance of integrating radiobiological assessments with physical dose metrics to inform the clinical application of advanced RT technologies. However, this study had several limitations. The use of a single radiation dose limited its clinical relevance, and the immediate post-irradiation assessments may not have captured delayed biological responses. Additionally, the small number of replicates may have reduced the study’s statistical power. Future studies incorporating dose fractionation schemes, time course analyses, and larger sample sizes are warranted to better simulate clinical conditions and further elucidate the radiobiological effects of advanced RT techniques.